Mindfulness and modification therapy for behavioral dysregulation: Results from a pilot study targeting alcohol use and aggression in women - Wupperman, Peggilee; Marlatt, G. Alan; Cunningham, Amy; Bowen, Sarah; Berking, Matthias; Mulvihill-Rivera, Nicole; Easton, Caroline (Journal of Clinical Psychology, 2012)
Objectives: Increasing evidence suggests that deficits in mindfulness (awareness, attentiveness, and acceptance of the present moment) play a role in a range of disorders involving behavioral dysregulation. This paper adds to that literature by describing a transdiagnostic psychotherapy (Mindfulness & Modification Therapy; MMT) developed to target behavioral dysregulation. Design: An open-treatment pilot-trial investigated the feasibility, acceptability, and pre-post effects of MMT targeting women (N = 14) court-referred for alcohol abuse/dependence and aggression. Results: Pre-post comparisons revealed significant decreases in alcohol use, drug use, and aggression. In addition, the retention rate was 93%. Conclusion: Preliminary evidence suggests that MMT is a feasible and acceptable treatment that decreases dysregulated behaviors such as substance use and aggression, while also potentially increasing retention. © 2011 Wiley Periodicals, Inc.
Created from Fastlane, Scopus look-up
Keywords: Aggression; Anger; Behavior dysregulation; Emotion regulation; Intervention; Mindfulness; Substance; Transdiagnostic